Clericist Catholic Authors and the Crystallization of Historical Memory of World War I in Lebanonist-Particularist Discourse, 1918–1922 - Walker , Dennis Patrick (Islamic Studies, 2009)
The First World War was a crisisfor pan-Catholic ideology in Lebanon. The Maronite and other Catholic intellectuals and journalists most dyed by Westerners saw millions of them kill each other and deplete their states for the long term. Christianity and the Catholic Church had not enabled Christians to resolve disputes constructively. Could so weakened a France now sustain any role as a “protector” of Lebanon’s Maronites and other Christians? The peril to the West during WWI, though, did make the Arab Catholic intellectuals turn a blind eye to the secularizing aspects that marginalized Christianity there, aspects which those intellectuals had assailed in peace-time. The collapse of the Ottoman Empire ended in acrimony the relations that the Maronites had built with the Turks, while leaving open friendship with Arab Muslims who had opposed the Turks.